Genotoxic effects of silver nanoparticles on lung cells - Reis, Corine Santos (2018)
Silver nanoparticles have increased importance due to their antimicrobial activity, being used in several applications such as in prosthesis, medical devices, food storing and cosmetics. Its increasing manufacturing will reflect in the environment, as for instance in the air, exposing the organism to its potential harmful effects. Altogether, the aim of this work was to evaluate the potential genotoxic effects of polyvinylpyrrolidone coated AgNPs. For that, a human alveolar adenocarcinoma cell line, A549, was exposed to increased concentrations of 0, 50 and 100 μg/mL PVP coated silver nanoparticles, of 10 and 20 nm, for 24h. Both the cytokinesis-block micronucleus cytome assay and the comet assay were used to evaluate the potential genotoxic effects of silver nanoparticles. To validate the cytokinesis-block micronucleus cytome assay, a human bone cell line, MG-63, was exposed to increased concentrations of 20 nm PVP coated silver nanoparticles. In A549 cell line, the comet assay revealed an increase in DNA damage, with increase concentration of silver nanoparticles of 10 nm. By other hand, for 20 nm AgNPs a significant increase in DNA damage was observed only for the lowest concentration (50 μg/mL). The cytokinesis-block micronucleus cytome assay showed a cytostatic effect of silver nanoparticles. In MG-63 cell line it was observed an increase in both micronucleus and nuclear buds for 50 μg/mL, indicating the presence of DNA damage. Altogether, the results suggest that PVP coated silver nanoparticles have the potential to induce DNA damage, dependent on the concentration and the size, and have a cytostatic effect on cells.